A 1860MPa grade hot-rolled V-containing high-strength wire rod for bridge cables and a manufacturing method thereof
By adopting V-containing overeutectoid steel composition system and online molten salt isothermal weak tempering treatment technology in the hot-rolled strips for 1860MPa grade bridge cables, the problems of mesh carbides and hard and brittle structures are solved, and the effect of high strength and plastic matching is achieved, meeting the wire making and torsional performance requirements of bridge cables are met.
Patent Information
- Application Number
- CN202411650078.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing 1860MPa-level bridge cables are hot-rolled strips to form mesh carbides and hard and brittle structures on the air-cooled line, resulting in unqualified brittle breakage and torsion, and the alloy costs are high, the strong plasticity is insufficient, and the mechanical properties fluctuate greatly.
Using a V-containing supereutectoid steel component system, through the online molten salt isothermal weak tempering treatment, the control strip quickly enters the soxunite phase region from the austenite state to form a fine sheet-spaced Soxunite structure, and the tissue is promoted for short-term tempering through the molten salt treatment in the latter section, avoiding the polymerization and coarsening of the nano-precipitated phase and enhancing strong plasticity.
It effectively avoids the formation of mesh carbides and hard and brittle tissues, improves the structural uniformity of the strip and the matching of strong plastic properties, reduces mechanical performance fluctuations, meets the requirements of wire making and torsion performance, and reduces production costs.
Smart Images

Figure CN119144801B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hot-rolled wire rods, and in particular relates to a hot-rolled V-containing high-strength wire rod for 1860MPa-grade bridge cables and a manufacturing method thereof. Background Art
[0002] As a typical variety of high-strength bridge cables, 1860MPa-grade bridge cables are generally made of hot-rolled wire rods that have been processed by pickling, phosphating, wire drawing, hot-dip galvanizing, stabilization and other deep processing. Improving the strength grade of bridge cables is beneficial to achieving lightweight and safety of bridges. Therefore, the performance requirements of hot-rolled wire rods, which directly affect the processing and finished product performance of bridge cables, have also increased. Improving the specifications of hot-rolled wire rods is also beneficial to further improve the strength of steel wires by increasing the surface reduction rate. At present, hot-rolled wire rods for 1860MPa-grade bridge cables are usually designed with 0.87% C content combined with appropriate amounts of strengthening elements such as Cr, Mn, and B, and are produced by Stelmor air-cooled lines after rolling to obtain wire rods with fine pearlite structure. However, there are still the following technical difficulties in manufacturing larger-sized hot-rolled wire rods with higher strength, better brittle fracture resistance and torsional performance:
[0003] 1. In order to improve the strength of wire rod, the C and Mn content in steel is relatively large, but it also aggravates the segregation in the metal solidification process, making it difficult to control the network carbides precipitated along the grain boundary on the air cooling line, thereby destroying the uniformity of the wire rod structure, increasing brittleness, and reducing plasticity and toughness, thereby causing wire breakage or torsion failure during drawing. Therefore, in order to minimize the precipitation of network carbides, the fan air volume will be increased after spinning, for example: Patent CN112458356B discloses a 1860MPa grade bridge cable galvanized steel wire for φ14mm wire rod and preparation method, adopt C-Si-Mn-Cr composition design combined with low temperature rolling and first fast and then slow cooling after spinning to obtain sorbitized structure and reduce the level of network carbides, but due to the limited maximum cooling capacity of the air cooling line, the time for the wire rod to pass through the secondary cementite precipitation interval is still relatively long, and the improvement effect is limited, while reducing the C and Mn contents will bring about a large strength loss, and reducing the air cooling strength after spinning will produce more network carbides, which is also not conducive to refining the pearlite lamellae and improving the matrix strength.
[0004] Second, in order to obtain finer pearlite structure, i.e., bainite structure, at a lower phase transformation temperature to improve the strength of the wire rod, the wire rod has a higher content of strengthening elements, which makes the wire rod have greater hardenability. At the same time, after spinning, in order to reduce the network carbide, the fan air volume is increased for rapid cooling, so that the temperature difference between the windward side and the leeward side of the wire rod, and from the upper edge to the core of the cross section when the specification is larger, is further increased. Affected by segregation and hardenability, some overcooled positions of the wire rod are more likely to form hard and brittle structures such as quenched martensite and bainite, which seriously affects the plasticity of the wire rod and increases the fluctuation of mechanical properties, resulting in brittle fracture of the wire rod in the wire making process and unqualified torsion process. Although the prior art discloses a technical means of improving the uniformity of the bainite structure by reheating the wire rod for austenitization after unwinding, and then subjecting the wire rod to salt bath treatment, so as to improve the torsion performance of the steel wire, it also increases the manufacturing process, production cycle, energy consumption, emissions and cost of bridge cables, which is not conducive to downstream production.
[0005] 3. In order to improve the strength and drawing performance of wire rod as much as possible, although low-temperature rolling and wire drawing are used to refine the grains, on the one hand, the rolling load will increase, the rolling speed will deteriorate, and the rolling efficiency will be affected when the billet specifications are large. On the other hand, the risk of forming network carbides after wire drawing will increase, and the incubation time of the microstructure phase transformation will be limited; and although the fan air volume will be reduced when approaching the phase transformation temperature to delay the cooling speed of the wire rod and extend the sorbite phase transformation time as much as possible to increase the sorbite content in the microstructure that is beneficial to strength and drawing, on the one hand, the minimum cooling of the air-cooled line The capacity is limited, and the addition of strengthening elements such as Si also prolongs the phase transformation time. The incubation time of the wire rod is limited during the continuous cooling process, and it is difficult to fully transform into the troostite structure, which limits the improvement of the troostite content and the strength of the wire rod. On the other hand, the troostite lamellae formed by the wire rod are still relatively coarse. The addition of strengthening elements such as Mn and Cr limits the activity of carbon and increases the difficulty of softening. After the phase transformation during the continuous cooling process, the low-temperature state has been processed, and the thermal driving force is insufficient, resulting in high organizational stress and dislocation density of the final wire rod. Although the strength is high, the plasticity is insufficient, which increases the risk of fracture during subsequent wire making and torsion.
[0006] Fourth, in order to further improve the wire rod, although trace alloys such as V are added to the composition to refine the austenite grains, the chemical driving force of the precipitation reaction under high temperature conditions during phase transformation is small, the precipitation nucleation occurs at the phase boundary, and the time at the peak precipitation temperature of the V-containing precipitation phase during the phase transformation is short, all of which limit the strengthening effect of V. Further increasing the V content will increase the material cost, which is not conducive to controlling the material cost of the wire rod. Summary of the invention
[0007] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a hot-rolled V-containing high-strength wire rod for 1860MPa bridge cables and a manufacturing method thereof, which can improve the problems of network carbides and hard-brittle structures, effectively utilize C and V elements, and improve the structural uniformity and strength-plasticity matching of large-size wire rods. It can be used for the manufacture of 1860MPa bridge cables to meet the requirements of wire making and torsion.
[0008] The technical solution adopted by the present invention to solve its technical problem is:
[0009] A method for manufacturing a 1860MPa grade hot-rolled V-containing high-strength wire rod for bridge cables, the manufacturing method comprising:
[0010] The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.84%~0.88%, Si: 0.36%~0.46%, Mn: 0.76%~0.86%, Cr: 0.15%~0.28%, V: 0.015%~0.035%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; the wire rod is rolled at a spinning temperature of ≥900°C After being spun into wire rods, they are subjected to online molten salt isothermal weak tempering treatment, whereby the wire rods first pass through the front section of molten salt and are cooled at a cooling rate of ≥35°C / s, entering the sorbite phase region from the austenite state to form a sorbite-dominated organization, and then undergo a rear section of molten salt heating to promote isothermal tempering of the organization and melting of the sorbite lamellae, and finally undergo roller slow cooling to produce a hot-rolled wire rod with a microstructure including tempered sorbite with a volume percentage of ≥93%, and the rest being a mixed organization consisting of ferrite and fused sorbite.
[0011] The design basis of the chemical composition and mass percentage of the above hot rolled wire rod includes:
[0012] (1) Carbon: As an effective carbide strengthening element and austenite forming element, C can improve the strength of wire rod by solid solution strengthening and precipitation of compounds with carbide forming elements. However, if the C content is too high, the central segregation and decarburization tendency of high carbon steel alloy billet will be aggravated, the control difficulty of abnormal structures such as grain boundary network carbides and martensite will increase, and the toughness of the material will deteriorate. Therefore, in order to take into account the high strength requirements of 1860MPa grade bridge cables and reduce the difficulty of controlling the uniformity of the structure, it is more conducive to refining the troostite lamellae during online molten salt isothermal weak tempering treatment and improving the strengthening effect of carbon elements. The mass percentage of C is controlled to be 0.84%~0.88%.
[0013] (2) Silicon: The Si element is often used as a deoxidizer during the smelting process. It will strengthen the material when dissolved in the ferrite phase. At the same time, it can inhibit the coarsening of cementite, which is beneficial to obtaining a finer troostite structure in the previous molten salt treatment. It can accelerate the diffusion rate of carbon, which is beneficial to promoting the rapid melting of troostite in the subsequent molten salt treatment and reducing the strength loss in the subsequent hot-dip galvanizing process of the steel wire. However, too high a silicon content will make the steel easier to decarburize when heated at high temperature and will prolong the phase change time, which is not conducive to the rapid phase change in the previous molten salt treatment. Therefore, the Si content is appropriately increased, and the mass percentage of Si is controlled to be 0.36%~0.46%.
[0014] (3) Manganese: Mn can be added as a deoxidizer in the steelmaking process, mainly playing a role in solid solution strengthening, while increasing the hardenability of the wire rod, reducing the phase transition temperature, and promoting the refinement of the interlamellar spacing of the sorbite structure to improve the matrix strength. However, when the Mn content is too high, it will increase the tendency of grain coarsening and component segregation, making it easier to form a low-temperature martensite structure, while reducing the diffusion activity of carbon, which is not conducive to promoting the rapid melting of sorbite and rapid softening during tempering during the subsequent molten salt treatment, thereby reducing the plasticity of the wire rod. Therefore, in order to take into account the high strength and plasticity of the hot-rolled wire rod, the mass percentage of Mn is controlled to be 0.76%~0.86%.
[0015] (4) Chromium: Cr is a medium-strong carbide-forming element in high carbon steel. It can improve the stability of austenite and the hardenability of wire rod, reduce the spacing between troostite lamellae, improve the matrix strength and the work hardening rate during wire drawing, and reduce the strength loss during the subsequent hot-dip galvanizing of steel wire. However, high Cr content will aggravate segregation, increase the risk of abnormal tissue precipitation and material cost, reduce the activity of carbon in steel, and be unfavorable for the rapid melting and tempering softening of troostite during the subsequent molten salt treatment, resulting in increased difficulty in improving plasticity. Therefore, the Cr content is appropriately reduced, and the mass percentage of Cr is controlled to be 0.15%~0.28%.
[0016] (5) Vanadium: As a microalloying element, V can refine austenite grains to improve the strength and toughness of the matrix. At the same time, it can form nanoscale precipitation phases at a medium temperature of 500-600°C. It can adapt to the online molten salt isothermal weak tempering treatment control and effectively improve the strength of the wire rod and its resistance to hydrogen-induced delayed fracture. However, if the temperature is too high or the online molten salt isothermal weak tempering treatment time is too long, it will cause the aggregation and coarsening of the nanoscale precipitation phases, which is not conducive to strength and plasticity. At the same time, the price is relatively high. Therefore, considering the role of V and material cost, the mass percentage of V is controlled to be 0.015%-0.035%.
[0017] (6) Phosphorus and sulfur: P and S are impurity elements. The lower the better. Therefore, P is controlled to be ≤ 0.015% and S is ≤ 0.015%.
[0018] The hot-rolled wire rod adopts C-Si-Mn-Cr-V composition design, and the hardenability of the wire rod is regulated by optimizing the ratio of each component, which provides favorable conditions for refining the spacing between sorbite lamellae, adjusting the sorbite precipitation temperature range to adapt to the dispersed precipitation temperature range of the V-containing precipitation phase, and reducing the difficulty of sorbite melting and organization softening. On this basis, the manufacturing method adopts a higher wire-spinning temperature to fully austenitize the wire rod, which can avoid the formation of network carbides due to too low temperature in the wire-spinning stage, and then performs online molten salt isothermal weak tempering weak tempering treatment:
[0019] First, compared with the Stelmor air-cooling line, the maximum cooling rate is limited, and the hypereutectoid steel composition system is easy to form network carbides on the air-cooling line. When the wire rod passes through the front molten salt, on the one hand, the high heat exchange capacity of the molten salt can be used to promote the rapid cooling of the wire rod from the high-temperature austenite state after spinning, effectively reducing the time for the wire rod to pass through the secondary cementite precipitation temperature range of 700~800℃, avoiding the precipitation of network carbides along the grain boundaries and deteriorating the plasticity and organizational uniformity of the wire rod, and improving the strengthening effect of the carbon element. On the other hand, it can form a larger degree of supercooling through rapid cooling, promote the rapid nucleation of troostite, combine with Si to inhibit the coarsening of cementite, reduce the spacing between troostite lamellae, improve the matrix strength, make up for the strength loss caused by reducing the Cr content, and provide favorable conditions for the short-term tempering of the molten salt in the later stage.
[0020] 2. Compared with the risk of precipitation of abnormal structures such as martensite and structural inhomogeneity caused by strong cooling of the Stelmor air-cooling line, on the one hand, when the wire rod passes through the front-stage molten salt, the molten salt can cover the surface of the wire rod for faster and more uniform heat exchange, and there is no temperature difference between the windward side and the leeward side. The temperature gradient from the edge to the core of the cross-section of the larger-sized wire rod can be further reduced through rapid heat exchange, and enter the troostite phase region and undergo phase transformation in accordance with the molten salt temperature, thereby promoting the full transformation of the troostite structure and forming a structure dominated by troostite with fine interlamellar spacing, so as to improve the troostite content and the uniformity of troostite distribution. On the other hand, the temperature can be appropriately raised when it is treated with the molten salt in the rear stage, so as to avoid the wire rod being overcooled due to segregation and hardenability to form abnormal bainite or martensite structures, or forming abnormal structures in the subsequent roller slow cooling process due to residual austenite, thereby further improving the structural uniformity. At the same time, compared with offline salt bath treatment, it can simplify the process, reduce costs and increase production capacity.
[0021] 3. Compared with the Stelmore air-cooled line, which limits the inoculation and softening of troostite and affects the dispersion and precipitation of V-containing nano-precipitates due to continuous cooling, on the one hand, when the wire rod is treated with the front-end molten salt, it can maintain a lower molten salt temperature and a longer treatment time, which can promote the refinement of the troostite structure and the rapid transformation of the austenite structure to troostite, making up for the adverse effect of increasing the Si content on prolonging the phase transformation time. At the same time, the lower temperature is suitable for the precipitation temperature of the V-containing precipitation phase and the driving force is greater, which can promote the refinement of the precipitation phase and nucleate inside the matrix, further improving the matrix strength. On the other hand, the rear-end molten salt is suitable for When the temperature is increased instead of continuously cooled, more thermal power can be provided, which can promote short-time isothermal tempering of the structure dominated by fine lamellar spacing troostite, melt the troostite lamellae, reduce the stress and dislocation density of the structure, and transform it into tempered troostite, toughen the structure, and regulate the plasticity of the wire rod through the tempering state, so that V can be dispersed and precipitated to form nano-scale precipitation phase. The consistency of the wire rod temperature with the molten salt also prevents the aggregation and coarsening of the nano-precipitation phase due to excessively high wire rod temperature or too long treatment time at the isothermal tempering temperature, thereby effectively improving the strengthening effect of V and further improving the overall strength and plasticity of the wire rod.
[0022] Since the temperature of the wire rod is relatively high after the latter stage of molten salt treatment, the subsequent slow cooling by rollers can reduce the cooling speed of the wire rod to avoid the reduction of plasticity of the wire rod due to rapid cooling. At the same time, slow cooling promotes further toughening of the wire rod structure, improves the softening effect of the wire rod, and achieves a match between high strength and plasticity of the wire rod.
[0023] Before the rolling, the appropriate heating furnace soaking temperature and furnace time can be selected to promote uniform diffusion of carbon and alloy elements and reduce segregation, and the furnace time and air-fuel ratio can be controlled to avoid decarburization of the steel billet. In a preferred embodiment, before the rolling, the heating furnace soaking temperature is controlled to be 1100-1140°C, the furnace time is 90-180min, and the air-fuel ratio is ≤0.55.
[0024] Controlling the descaling pressure before rolling can prevent the oxide scale on the surface of the steel billet after heating in the heating furnace from being pressed into the wire rod and affecting the surface quality of the wire rod. In a preferred embodiment, before rolling, the descaling pressure is controlled to be ≥18MPa.
[0025] Since the soaking temperature of the heating furnace is relatively high, selecting a higher initial rolling temperature can reduce the deformation resistance of the steel billet and the load on the rolling mill. Appropriate initial rolling reduction can be used to avoid grain growth and decarburization caused by excessive initial rolling temperature. In a preferred embodiment, during the rolling, the initial rolling temperature is controlled to be 1040~1080℃, and the initial rolling reduction is 25%~30%.
[0026] Under appropriate rolling temperature and reduction, the rolling speed can be increased to further improve the rolling efficiency. In a preferred embodiment, during the rolling, the rolling speed is controlled to be ≥30 m / s.
[0027] Due to the high spinning temperature, the selection of appropriate rolling temperature and reduction can control the wire size accuracy, and at the same time promote dynamic recrystallization during the final rolling process to refine the grains and strengthen the matrix. In a preferred embodiment, during the rolling, the final rolling temperature is controlled to be 920~960℃, and the final rolling reduction is 27%~32%.
[0028] The molten salt temperature of the front stage molten salt is in the troostite phase region. At the same time, the lower the molten salt temperature and the longer the processing time, the finer the spacing between the troostite lamellae formed, the more complete the troostite phase transformation, and the more power can be provided for the dispersion precipitation of V, so that the matrix strength is improved. However, if the molten salt temperature is too low, the precipitation phase of V cannot be precipitated, the strength of the wire rod is lost, and even entering the bainite phase region will produce abnormal bainite structure that increases the brittleness of the wire rod, and the plasticity of the wire rod is lost. If the processing time is too long, the production energy consumption will be increased, and it will be unfavorable to control the polymerization of the dispersed precipitation phase. On the contrary, if the molten salt temperature is higher and the processing time is shorter, the spacing between the troostite lamellae formed will increase, the plasticity of the matrix will increase, but the molten salt Too high temperature is not conducive to the rapid nucleation of troostite with fine lamellar spacing, and will increase the difficulty of softening. Too short treatment time is not conducive to improving the troostite content in the organization and controlling the large-scale dispersed precipitation of V-containing precipitates, which will affect the wire rod organization control and lose the wire rod strength. Therefore, the molten salt temperature and treatment time of the front-stage molten salt can be further controlled to promote the wire rod to form a organization dominated by troostite with fine lamellar spacing, promote the dispersed precipitation of V-containing precipitates, so as to improve the matrix strength and provide favorable conditions for short-time tempering in the rear-stage molten salt treatment. In a preferred embodiment, the molten salt temperature of the front-stage molten salt is 510~540℃, and the treatment time is 35~55s.
[0029] Since the temperature difference from the spinning temperature to the troostite phase temperature of the wire rod is large, a higher molten salt circulation rate is selected in the front stage to reduce the temperature rise of the molten salt, which can further improve the uniformity of the structure and promote the nucleation of troostite with fine lamellar spacing. In a preferred embodiment, the molten salt circulation rate of the front stage molten salt is 550~680t / h, and the temperature rise of the molten salt is ≤10℃.
[0030] The molten salt temperature of the rear-stage molten salt is appropriately increased relative to that of the front-stage molten salt. At the same time, the higher the molten salt temperature and the longer the treatment time, the more thermal power can be provided for the tempering and softening of the wire rod structure, which can promote the melting of the sorbite lamellae, form tempered sorbite and melted sorbite, and improve the plasticity of the matrix. However, if the molten salt temperature is too high, the structure is too softened, which is not conducive to the precipitation and refinement of the V-containing precipitate phase, and the strength of the wire rod will be lost. If the treatment time is too long, the polymerization and coarsening of the nano-scale precipitate phase will be caused, which will lose the strong and plastic properties and increase the production energy consumption. On the contrary, the lower the molten salt temperature and the longer the treatment time, the more thermal power can be provided for the tempering and softening of the wire rod structure, which can promote the melting of the sorbite lamellae, form tempered sorbite and melted sorbite, and improve the plasticity of the matrix. However, if the molten salt temperature is too high and the structure is too softened, it will be unfavorable for the precipitation and refinement of the V-containing precipitate phase, and the strength of the wire rod will be lost. If the treatment time is too long, the polymerization and coarsening of the nano-scale precipitate phase will be caused, and the strong and plastic properties will be lost, and the production energy consumption will be increased. The shorter the treatment time, the lower the toughening and softening effects of the structure, and the plasticity of the wire rod decreases. However, if the molten salt temperature is too low and the treatment time is too short, it is not conducive to the melting of the troostite lamellae and the precipitation of the V-containing precipitation phase along the phase boundary, which will cause a loss of strength and plasticity. Therefore, the molten salt temperature and treatment time of the rear-stage molten salt can be further controlled to regulate the tempering of the structure and the rapid melting of the troostite lamellae while avoiding the polymerization and coarsening of the nano-precipitation phase. In a preferred embodiment, the molten salt temperature of the rear-stage molten salt is 550~590℃, and the treatment time is 50~150s.
[0031] Since the temperature difference between the front-end molten salt and the rear-end molten salt of the wire rod is small, the molten salt circulation volume of the rear-end molten salt is appropriately reduced. Accurate temperature control can also reduce production energy consumption. In a preferred embodiment, the molten salt circulation volume of the rear-end molten salt is 350~460t / h, and the molten salt temperature rise is ≤4°C.
[0032] In a preferred embodiment, the roller slow cooling controls the wire rod to be cooled to below 300°C at a slow cooling rate of ≤1.5°C / s for coiling, which can avoid the reduction of plasticity of the wire rod due to rapid cooling and improve the softening effect of the wire rod.
[0033] In a preferred embodiment, the roller slow cooling control adopts an open insulation cover, and the wire rod is transported by the roller into the insulation cover, which can help the wire rod's own residual temperature control the slow cooling speed, help increase the roller conveying rate, promote rapid offline, and improve production efficiency.
[0034] A hot-rolled V-containing high-strength wire rod for 1860MPa grade bridge cables, wherein the hot-rolled wire rod is manufactured by any of the above-mentioned methods for manufacturing the hot-rolled V-containing high-strength wire rod for 1860MPa grade bridge cables.
[0035] The hot-rolled wire rod adopts a hypereutectoid steel component system containing trace V elements. Compared with the existing high-carbon stranded wire steel wire rod, it is easy to form a network of carbides and hard-brittle phase structures. The formed troostite structure has a low content and large fluctuations in mechanical properties and stress. The microstructure of the hot-rolled wire rod is mainly tempered troostite, containing a small amount of ferrite and fused troostite. The troostite lamellae have finer spacing and higher content, and have better strength and drawing properties than pearlite structures. After tempering and lamella melting and transformation into tempered troostite and fused troostite, the organizational stress and dislocation density become lower, so that the organization is toughened. Combined with the large amount of dispersed precipitation and uniform distribution of V-containing precipitates, while improving the uniformity of the organization, it can make up for the strength loss caused by reducing the Cr content, and further improve the matrix strength, while reducing the difficulty of plasticity improvement. The tempered state is used to regulate the matching of organizational plasticity with high-strength performance, which is beneficial to improving the strength of the bridge cable steel wire and reducing the risk of fracture of the wire rod in subsequent wire making and torsion processes.
[0036] The finer the tempered troostite lamellae spacing is, the higher the matrix strength is. However, if the tempered troostite lamellae spacing is too fine, it will be more difficult to control the large-scale precipitation of V-containing precipitates and the precipitation of abnormal structures. In a preferred embodiment, the tempered troostite lamellae spacing is 75-120 nm.
[0037] In a preferred embodiment, the network carbide level of the hot-rolled wire rod is level 0, which can effectively prevent the carbon element from generating abnormal network carbide structure, enhance the strengthening effect of the carbon element, and enhance the overall strength and plasticity of the wire rod.
[0038] The hot-rolled wire rod can avoid the risk of abnormal network carbides and martensite structures, improve the uniformity of mixed structure distribution, and thus reduce the fluctuation of mechanical properties, which is beneficial to improving the torsional properties of steel wire made of wire rod. In a preferred embodiment, the mechanical property difference of the hot-rolled wire rod is ≤40MPa.
[0039] In a preferred embodiment, the hot-rolled wire rod has a diameter of 12.0~15.0mm, a tensile strength of 1340~1390MPa, and a cross-sectional shrinkage rate of 38%~43%. The hot-rolled wire rod has a larger diameter specification, and the strength of the bridge cable steel wire can be increased by increasing the area reduction rate or manufacturing larger specifications of bridge cable steel wire, simplifying the manufacturing of bridge cables. The wire rod has a large tensile strength, can quickly reach the target strength and reduce the strength loss effect of hot-dip galvanizing. The wire rod has a high cross-sectional shrinkage rate, which makes the wire rod have higher plastic toughness, can reduce the risk of wire breakage during deep drawing and torsion, and improve the yield rate.
[0040] Compared with the prior art, the beneficial effects of the present invention are at least:
[0041] (1) In view of the fact that the existing 1860MPa grade hot-rolled wire rod for bridge cables is prone to form network carbides and hard and brittle structures such as quenched martensite and bainite on the air cooling line, resulting in brittle fracture of the wire rod in the wire making process and unqualified torsion process, the manufacturing method of the present invention adopts a V-containing hypereutectoid steel component system combined with an online molten salt isothermal weak tempering and weak tempering technology. The front-stage molten salt can control the wire rod to quickly skip the network carbide precipitation zone from the high-temperature austenite state and enter the sorbite phase zone, forming a structure dominated by sorbite with fine lamellar spacing. The V-containing precipitate phase forms a large number of nano-scale precipitates at medium temperature. The rear-stage molten salt can provide more thermal power, which can control the wire rod structure for short-time tempering and avoid the aggregation and coarsening of the nano-precipitate phase, thereby improving the strength and plasticity of the wire rod. The wire rod structure is further toughened by slow cooling through a roller, thereby improving the structure uniformity and strength and plasticity matching of large-size wire rods, and has good industrial adaptability.
[0042] (2) In view of the current situation that the hot-rolled wire rod alloy for 1860MPa bridge cables is of high cost, insufficient strength and plasticity, and large fluctuations in mechanical properties, the hot-rolled wire rod of the present invention adopts a C-Si-Mn-Cr-V composition design with low Cr and V contents, which can effectively avoid the risk of abnormal structures such as net carbon and martensite produced by C elements. The microstructure is mainly tempered troostite with a small amount of ferrite and fused troostite, which can increase the proportion of tempered troostite, effectively utilize the strengthening effect of C and V elements, promote the refinement of V-containing precipitation phase and a large amount of dispersed precipitation, further improve the matrix strength, use the tempered state to promote further toughening of the wire rod structure, adjust the plasticity of the structure to match the high-strength performance, reduce the fluctuations in mechanical properties, and achieve a tensile strength of 1340~1390MPa and a cross-sectional shrinkage of 38%~43%. It is used in the manufacture of 1860MPa bridge cables and other application fields, can meet the requirements of wire making and torsion performance, and has good industrial adaptability.
[0043] (3) The manufacturing method of the present invention can further reduce the limitation of the spinning temperature on the rolling process, select appropriate rolling temperature and deformation, control decarburization, improve rolling efficiency, and promote dynamic recrystallization and grain refinement in the final rolling process; further control the wire rod slow cooling speed in the roller slow cooling process, promote the rapid offline of the wire rod, improve production efficiency, and have good industrial adaptability. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0045] Figure 1 is a metallographic structure diagram of Example 1 of the present invention;
[0046] Figure 2 is the metallographic structure diagram of Example 2 of the present invention;
[0047] Figure 3 It is the metallographic structure diagram of Example 3 of the present invention. DETAILED DESCRIPTION
[0048] The embodiments described below with reference to the accompanying drawings are exemplary and are only for illustration and do not limit the description of the features and characteristics of the present invention, so as to propose the best way to implement the present invention, and are intended to be used to explain the present invention and are sufficient to enable those skilled in the art to implement the present invention, but cannot be understood as any limitation on the scope of the present invention, which is limited only by the appended claims; the organization and performance testing of the hot-rolled wire rods obtained in the following embodiments and comparative examples include: the tensile test is carried out using "GB-T 228.1-2021 Metallic Material Tensile Test Part 1: Room Temperature Test Method" to obtain the tensile strength and cross-sectional reduction rate; the organization test is carried out according to the metal microstructure detection method of GB / T13298 standard; the mechanical property same circle difference test method: take 2 circles of wire rod 5m away from the end of the coil, take the overlap area position as the base point, divide each circle of wire rod into 8 sections on average, take 1 tensile specimen on each section, and the strength extreme difference of the tensile specimen after the tensile test is the mechanical property same circle difference. Embodiment 1:
[0049] A preferred embodiment of the method for manufacturing the 1860MPa grade hot-rolled V-containing high-strength wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.84%, Si: 0.39%, Mn: 0.77%, Cr: 0.15%, V: 0.035%, P: 0.013%, S: 0.012%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt isothermal weak tempering → roller slow cooling → coiling, specifically:
[0050] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote the uniform diffusion of carbon and alloy elements in the steel billet, and avoid decarburization of the steel billet. After the steel billet leaves the heating furnace, high-pressure dephosphorization water is used to remove the oxide scale on the surface of the steel billet, and then the steel billet is rolled into a wire with a diameter of 12mm through a rolling line. Appropriate rolling temperature, reduction amount and rolling speed are selected to control decarburization and promote rapid rolling, and control the dynamic recrystallization and grain refinement during the final rolling process. Specifically: the heating furnace is controlled to have a soaking temperature of 1115°C, and the furnace time is controlled to have a quenching rate of 150°C. The rolling speed is 10m / s, the rolling time is 155min, the air-fuel ratio is ≤0.53, the descaling pressure is 19MPa, the initial rolling temperature is 1055℃, the initial rolling reduction is 30%, the final rolling temperature is 935℃, the final rolling reduction is 32%, and the rolling speed is 30m / s; the spinning process is used to make the wire rod out of the rolling line into a wire rod through a spinning mechanism, and the wire rod is spread on the roller and transported along the roller. An appropriate spinning temperature is selected to austenitize the wire rod to prevent the precipitation of network carbides in the spinning stage, so as to form a large degree of supercooling later, thereby promoting the rapid nucleation of troostite with fine interlamellar spacing, and specifically: the spinning temperature is controlled to be 910℃.
[0051] The online molten salt isothermal weak tempering process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for the front stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 37°C / s, and quickly skips the network carbide precipitation interval from the high-temperature austenite state to enter the sorbite phase area, inhibits the formation of network carbides, promotes the austenite phase transformation to form a structure dominated by sorbite with fine lamellar spacing, and a large amount of V-containing carbides are dispersed and precipitated, thereby improving the strength of the matrix. Then, it is conveyed by a roller through the second stage salt bath tank for the rear stage Molten salt treatment, appropriately increase the molten salt temperature, reduce the molten salt circulation volume, promote short-time isothermal tempering of the organization, and melting of the sorbite lamellae, avoid causing polymerization and coarsening of the nano-precipitation phase, and improve the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature of the front section molten salt is 510°C, the treatment time is 55s, the molten salt circulation volume is 680t / h, and the molten salt temperature rise is ≤10°C; the molten salt temperature of the rear section molten salt is 550°C, the treatment time is 150s, the molten salt circulation volume is 385t / h, and the molten salt temperature rise is ≤4°C.
[0052] The roller slow cooling process uses an open insulation cover, and the wire rod that has passed through the second salt bath tank is transported by the conveyor roller into the insulation cover to promote further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 290°C at a slow cooling rate of 1.1°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 1 shown.
[0053] Comparative Example 1:
[0054] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 1 in that: the manufacturing method is manufactured according to the process flow of rolling → spinning → Stelmor air cooling, specifically: the heating furnace soaking temperature is controlled to be 1080°C, the furnace time is 200min, the initial rolling temperature is 1000°C, the final rolling temperature is 890°C, the rolling speed is 27m / s, and the spinning temperature is 865°C; the Stelmor strong air cooling adopts an air volume of 260,000 m per fan. 3 / h, open 1~6# fans at 80%, cool the wire rod to 655℃ at a cooling rate of 8.2℃ / s, and then open 6~14# fans at 15%, cool the wire rod to 282℃ at a cooling rate of 3.1℃ / s, and obtain the hot-rolled wire rod product after it comes off the line.
[0055] Comparative Example 2:
[0056] A method for manufacturing a hot-rolled wire rod, which differs from Example 1 in that: the heating furnace soaking temperature is controlled to be 1090°C, the furnace time is 180min, the initial rolling temperature is 1015°C, the final rolling temperature is 905°C, the rolling speed is 28m / s, the spinning temperature is 885°C, during the front-stage molten salt treatment, the wire rod is cooled at a cooling rate of 33°C / s, and the hot-rolled wire rod finished product is obtained after it is off the line. Embodiment 2:
[0057] A preferred embodiment of the method for manufacturing the 1860MPa grade hot-rolled V-containing high-strength wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.84%, Si: 0.46%, Mn: 0.81%, Cr: 0.22%, V: 0.032%, P: 0.013%, S: 0.012%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt isothermal weak tempering → roller slow cooling → coiling, specifically:
[0058] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote the uniform diffusion of carbon and alloy elements in the steel billet, and avoid decarburization of the steel billet. After the steel billet leaves the heating furnace, high-pressure dephosphorization water is used to remove the oxide scale on the surface of the steel billet, and then the steel billet is rolled into a wire with a diameter of 13mm through a rolling line. Appropriate rolling temperature, reduction amount and rolling speed are selected to control decarburization and promote rapid rolling, and the dynamic recrystallization and grain refinement of the final rolling process are controlled. Specifically: the heating furnace is controlled to have a soaking temperature of 1100°C, and the furnace time is 100°C. The time is 180min, the air-fuel ratio is ≤0.5, the descaling pressure is 18MPa, the initial rolling temperature is 1040℃, the initial rolling reduction is 29%, the final rolling temperature is 920℃, the final rolling reduction is 30%, and the rolling speed is 31m / s; the wire-spinning process is used to make the wire rod out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. An appropriate wire-spinning temperature is selected to austenitize the wire rod to prevent the precipitation of network carbides in the wire-spinning stage, so as to form a large degree of supercooling later, thereby promoting the rapid nucleation of troostite with fine interlamellar spacing, and specifically: the wire-spinning temperature is controlled to be 900℃.
[0059] The online molten salt isothermal weak tempering process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for the front stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 35°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to enter the sorbite phase area, inhibiting the formation of network carbides, promoting the austenite phase transformation to form a structure dominated by sorbite with fine lamellar spacing, and a large amount of V-containing carbides are dispersed and precipitated, thereby improving the strength of the matrix, and then conveyed by a roller through the second stage salt bath tank for the rear stage Molten salt treatment, appropriately increase the molten salt temperature, reduce the molten salt circulation volume, promote short-time isothermal tempering of the organization, troostite lamellar melting, avoid the polymerization and coarsening of the nano-precipitation phase, and improve the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature of the front section molten salt is 519°C, the processing time is 51s, the molten salt circulation volume is 580t / h, and the molten salt temperature rise is ≤10°C; the molten salt temperature of the rear section molten salt is 578°C, the processing time is 116s, the molten salt circulation volume is 400t / h, and the molten salt temperature rise is ≤4°C.
[0060] The roller slow cooling process uses an open insulation cover, and the wire rod that has passed through the second salt bath tank is transported by the conveyor roller into the insulation cover to promote further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 284°C at a slow cooling rate of 1.2°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 2 shown.
[0061] Comparative Example 3:
[0062] A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that during the front-stage molten salt treatment, the wire rod is cooled at a cooling rate of 31°C / s, the molten salt temperature of the front-stage molten salt is 558°C, the treatment time is 28s, and a hot-rolled wire rod finished product is obtained after going offline.
[0063] Comparative Example 4:
[0064] A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that during the front-stage molten salt treatment, the wire rod is cooled at a cooling rate of 37°C / s, the molten salt temperature of the front-stage molten salt is 595°C, the treatment time is 60s, and a hot-rolled wire rod finished product is obtained after going offline. Embodiment 3:
[0065] A preferred embodiment of the method for manufacturing the 1860MPa grade hot-rolled V-containing high-strength wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.88%, Si: 0.36%, Mn: 0.76%, Cr: 0.27%, V: 0.026%, P: 0.015%, S: 0.015%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt isothermal weak tempering → roller slow cooling → coiling, specifically:
[0066] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote the uniform diffusion of carbon and alloy elements in the steel billet, and avoid decarburization of the steel billet. After the steel billet leaves the heating furnace, high-pressure dephosphorization water is used to remove the oxide scale on the surface of the steel billet, and then the steel billet is rolled into a wire with a diameter of 14mm through a rolling line. Appropriate rolling temperature, reduction amount and rolling speed are selected to control decarburization and promote rapid rolling, and the dynamic recrystallization and grain refinement of the final rolling process are controlled. Specifically: the heating furnace is controlled to have a soaking temperature of 1125°C, and the furnace time is 115min, air-fuel ratio ≤0.52, descaling pressure of 18MPa, initial rolling temperature of 1065℃, initial rolling reduction of 27%, final rolling temperature of 950℃, final rolling reduction of 29%, rolling speed of 31.5m / s; the spinning process is used to make the wire rod out of the rolling line into wire rod through the spinning mechanism, the wire rod is spread on the roller and transported along the roller, and an appropriate spinning temperature is selected to austenitize the wire rod to prevent the precipitation of network carbides in the spinning stage, so as to form a large degree of supercooling later, thereby promoting the rapid nucleation of troostite with fine interlayer spacing, and specifically: the spinning temperature is controlled to be 920℃.
[0067] The online molten salt isothermal weak tempering process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for the front stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 36°C / s, and quickly skips the network carbide precipitation interval from the high-temperature austenite state to enter the sorbite phase area, inhibits the formation of network carbides, promotes the austenite phase transformation to form a structure dominated by sorbite with fine lamellar spacing, and a large amount of V-containing carbides are dispersed and precipitated, thereby improving the strength of the matrix. Then, it is conveyed by a roller through the second stage salt bath tank for the post-molten salt treatment. The molten salt treatment in the front section is to appropriately increase the molten salt temperature and reduce the molten salt circulation volume, promote short-time isothermal tempering of the organization and melting of the sorbite lamellar layers, avoid the polymerization and coarsening of the nano-precipitation phase, and improve the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature of the front section is 531°C, the treatment time is 42s, the molten salt circulation volume is 610t / h, and the molten salt temperature rise is ≤10°C; the molten salt temperature of the rear section is 590°C, the treatment time is 72s, the molten salt circulation volume is 460t / h, and the molten salt temperature rise is ≤4°C.
[0068] The roller slow cooling process uses an open insulation cover, and the wire rod that has passed through the second salt bath tank is transported by the conveyor roller into the insulation cover to promote further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 280°C at a slow cooling rate of 1.5°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure diagram is as follows Figure 3 shown.
[0069] Comparative Example 5:
[0070] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that the molten salt temperature of the rear-stage molten salt is 605° C., the processing time is 160 s, and a hot-rolled wire rod finished product is obtained after the production line is off.
[0071] Comparative Example 6:
[0072] A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that the molten salt temperature of the rear-stage molten salt is 545° C., the processing time is 45 seconds, and a hot-rolled wire rod finished product is obtained after going offline. Embodiment 4:
[0073] A preferred embodiment of the method for manufacturing the 1860MPa grade hot-rolled V-containing high-strength wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.85%, Si: 0.43%, Mn: 0.86%, Cr: 0.27%, V: 0.015%, P: 0.015%, S: 0.012%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt isothermal weak tempering → roller slow cooling → coiling, specifically:
[0074] The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity, control the parameters of the heating furnace to promote the uniform diffusion of carbon and alloy elements in the steel billet, and avoid decarburization of the steel billet. After the steel billet leaves the heating furnace, high-pressure dephosphorization water is used to remove the oxide scale on the surface of the steel billet, and then the steel billet is rolled into a wire with a diameter of 15mm through a rolling line. Appropriate rolling temperature, reduction amount and rolling speed are selected to control decarburization and promote rapid rolling, and the dynamic recrystallization and grain refinement of the final rolling process are controlled. Specifically: the heating furnace is controlled to have a soaking temperature of 1140°C, and the furnace time is 150°C. The time is 90min, the air-fuel ratio is ≤0.55, the descaling pressure is 19MPa, the initial rolling temperature is 1080℃, the initial rolling reduction is 25%, the final rolling temperature is 960℃, the final rolling reduction is 27%, and the rolling speed is 32m / s; the wire-spinning process is used to make the wire rod out of the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on the roller and transported along the roller. An appropriate wire-spinning temperature is selected to austenitize the wire rod to prevent the precipitation of network carbides in the wire-spinning stage, so as to form a large degree of supercooling later, thereby promoting the rapid nucleation of troostite with fine interlamellar spacing, and specifically: the wire-spinning temperature is controlled to be 925℃.
[0075] The online molten salt isothermal weak tempering process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for the front stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 35°C / s, and quickly skips the network carbide precipitation interval from the high-temperature austenite state to enter the sorbite phase area, inhibits the formation of network carbides, promotes the austenite phase transformation to form a structure dominated by sorbite with fine lamellar spacing, and a large amount of V-containing carbides are dispersed and precipitated to improve the matrix strength. Then, it is conveyed by a roller through the second stage salt bath tank for the post-molten salt treatment. The molten salt treatment in the front section is to appropriately increase the molten salt temperature and reduce the molten salt circulation volume, promote short-time isothermal tempering of the organization and melting of the sorbite lamellar layers, avoid the polymerization and coarsening of the nano-precipitation phase, and improve the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature of the front section is 540°C, the treatment time is 35s, the molten salt circulation volume is 550t / h, and the molten salt temperature rise is ≤10°C; the molten salt temperature of the rear section is 565°C, the treatment time is 50s, the molten salt circulation volume is 460t / h, and the molten salt temperature rise is ≤4°C.
[0076] The roller slow cooling process uses an open insulation cover, and the wire rod that has passed through the second salt bath tank is transported by the conveyor roller into the insulation cover, which promotes further toughening of the wire rod structure and improves the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 295°C at a slow cooling rate of 0.95°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage.
[0077] Comparative Example 7:
[0078] A method for manufacturing a hot-rolled wire rod, which differs from Example 4 in that: the method is manufactured according to a process flow of rolling → spinning → online molten salt isothermal weak tempering → air cooling, wherein the air cooling is performed by opening a heat preservation cover and conveying the wire rod through a second salt bath tank by a conveyor roller, and the wire rod is cooled to 292°C at a slow cooling rate of 1.9°C / s; after the wire rod is off the line, a finished hot-rolled wire rod is obtained.
[0079] The hot rolled wire rods obtained in the above examples 1 to 4 and comparative examples 1 to 7 were subjected to microstructure and performance testing, and the comparative results obtained are shown in Table 1 below:
[0080] Table 1. Comparison of microstructure and performance of hot rolled wire rods with different compositions and manufacturing methods
[0081]
[0082] From the comparison results of Example 1 and Comparative Example 1, it can be seen that compared with the C-Si-Mn-Cr-V component system, the Stelmor air-cooled line is often used for production, which often weakens the strengthening effect due to the uncontrollable cooling rate during the cooling phase transformation process, and leads to the generation of abnormal tissues such as network carbon and martensite, which limits the improvement of the troostite content and the strength of the wire rod, causing the increase of mechanical property fluctuations. The present invention combines the online molten salt isothermal weak tempering technology, and the front-stage molten salt can control the wire rod to quickly skip the network carbide precipitation interval from the high-temperature austenite state to the troostite phase. zone, forming a structure dominated by troostite with fine lamellar spacing, the molten salt in the latter stage can provide more thermal power, control the wire rod structure for short-time isothermal tempering, and promote the refinement of V-containing precipitation phase and a large amount of dispersed precipitation, so as to adjust the matching of organizational plasticity and high-strength performance. It can be seen from the results of Examples 1 to 4 that the hot-rolled wire rod of the present invention can achieve a tensile strength of 1340 to 1390 MPa and a cross-sectional shrinkage rate of 38% to 43%, has high-strength characteristics, and is used for manufacturing 1860 MPa-level bridge cables and other application fields to meet the requirements of silk making and torsion.
[0083] From the comparison results of Example 1 and Comparative Example 2, it can be seen that by adopting a higher spinning temperature to fully austenitize the wire rod, the formation of network carbides due to too low temperature in the spinning stage can be avoided, which is beneficial to the nucleation of sorbite and can also reduce the limitation of the spinning temperature on the rolling process, which is beneficial to improving the rolling efficiency.
[0084] From the comparison results of Example 2 and Comparative Example 3, it can be seen that the higher the molten salt temperature of the front-stage molten salt and the shorter the treatment time, the larger the spacing between the formed troostite lamellae and the higher the plasticity of the matrix. However, too high a molten salt temperature is not conducive to the rapid nucleation of troostite with fine lamellae spacing, which will increase the difficulty of softening. Too short a treatment time is not conducive to increasing the troostite content in the organization and controlling the large-scale dispersed precipitation of V-containing precipitates, which further reduces the strength of the wire rod.
[0085] From the comparison results of Example 2 and Comparative Example 4, it can be seen that the lower the molten salt temperature of the front-stage molten salt and the longer the treatment time, the finer the spacing between the formed troostite lamellae, the more complete the troostite phase transformation, and the more power can be provided for the dispersion precipitation of V, so that the matrix strength is improved. However, if the molten salt temperature is too low, the precipitation of V-containing carbides will be affected, the strength of the wire rod will be lost, and the production of bainite structure will increase the difficulty of softening and lose the plasticity of the wire rod, which is not conducive to rapid production.
[0086] From the comparison results of Example 3 and Comparative Example 5, it can be seen that the higher the molten salt temperature of the rear-stage molten salt and the longer the treatment time, the more thermal power can be provided for the tempering and softening of the wire rod structure, which can promote the melting of the troostite lamellae and improve the plasticity of the matrix. However, if the molten salt temperature is too high, the treatment time is too long, and the structure is too softened, it is not conducive to the precipitation and refinement of the V-containing precipitation phase, causing the aggregation and coarsening of the nano-scale precipitation phase, which will result in the loss of strength and plasticity.
[0087] From the comparison results of Example 3 and Comparative Example 6, it can be seen that the lower the molten salt temperature of the rear-stage molten salt and the shorter the treatment time, the lower the toughening and softening effects of the structure and the plasticity of the wire rod. However, if the molten salt temperature is too low and the treatment time is too short, it is not conducive to the melting of the troostite lamellar and the precipitation of the V-containing precipitation phase along the phase boundary, which will cause a loss of strength and plasticity.
[0088] From the comparison results of Example 4 and Comparative Example 7, it can be seen that the use of roller slow cooling can reduce the cooling rate of the wire rod and avoid the reduction of plasticity of the wire rod due to rapid cooling. At the same time, slow cooling promotes further toughening of the wire rod structure and improves the softening effect of the wire rod.
[0089] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for manufacturing a 1860MPa grade hot-rolled V-containing high-strength wire rod for bridge cables, characterized in that: The manufacturing method thereof comprises: The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.84%-0.88%, Si: 0.36%-0.46%, Mn: 0.76%-0.86%, Cr: 0.15%-0.28%, V: 0.015%-0.035%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; after the wire rod is spun into a wire rod at a spinning temperature of ≥900°C, it is subjected to an online molten salt isothermal weak tempering treatment, so that the wire rod is first subjected to a front-stage molten salt and is annealed at 100°C. The steel is cooled at a cooling rate of ≥35°C / s, from the austenite state into the sorbite phase region, to form a structure dominated by sorbite, and then the temperature of the molten salt in the latter stage is promoted to carry out isothermal tempering of the structure and melting of the sorbite lamellae, and finally slowly cooled by a roller to produce a hot-rolled wire rod having a microstructure including a mixed structure of tempered sorbite with a volume percentage of ≥93% and the rest being ferrite and fused sorbite; the molten salt temperature of the former stage molten salt is 510-540°C, and the processing time is 35-55s; the molten salt temperature of the latter stage molten salt is 550-590°C, and the processing time is 50-150s.
2. The method for manufacturing the 1860MPa grade hot-rolled V-containing high-strength wire rod for bridge cables according to claim 1, characterized in that: Before the rolling, the soaking temperature of the heating furnace is controlled to be 1100-1140° C., the time in the furnace is 90-180 min, the air-fuel ratio is ≤0.55, and the descaling pressure is ≥18 MPa.
3. The method for manufacturing the 1860MPa grade hot-rolled V-containing high-strength wire rod for bridge cables according to claim 1, characterized in that: During the rolling, the initial rolling temperature is controlled to be 1040-1080° C., the initial rolling reduction is 25%-30%, and the rolling speed is ≥30 m / s.
4. The method for manufacturing the 1860MPa grade hot-rolled V-containing high-strength wire rod for bridge cables according to claim 3, characterized in that: During the rolling, the final rolling temperature is controlled to be 920-960° C., and the final rolling reduction is 27%-32%.
5. The method for manufacturing the 1860MPa grade hot-rolled V-containing high-strength wire rod for bridge cables according to claim 1, characterized in that: The molten salt circulation volume of the front-stage molten salt is 550-680 t / h, and the molten salt temperature rise is ≤10°C; the molten salt circulation volume of the rear-stage molten salt is 350-460 t / h, and the molten salt temperature rise is ≤4°C.
6. The method for manufacturing the 1860MPa grade hot-rolled V-containing high-strength wire rod for bridge cables according to claim 1, characterized in that: The roller slow cooling controls the wire rod to be cooled to below 300° C. at a slow cooling rate of ≤1.5° C. / s for coiling.
7. A 1860MPa grade hot-rolled V-containing high-strength wire rod for bridge cables, characterized in that: The hot-rolled wire rod is manufactured by the method for manufacturing the hot-rolled V-containing high-strength wire rod for 1860MPa grade bridge cables as described in any one of claims 1 to 6.
8. The 1860MPa grade hot-rolled V-containing high-strength wire rod for bridge cables according to claim 7, characterized in that: The interlamellar spacing of the tempered bainite is 75-120 nm, the network carbide grade of the hot-rolled wire rod is grade 0, and the mechanical property difference is ≤40 MPa.
9. The 1860MPa grade hot-rolled V-containing high-strength wire rod for bridge cables according to claim 7, characterized in that: The hot-rolled wire rod has a diameter of 12.0-15.0 mm, a tensile strength of 1340-1390 MPa, and a cross-sectional shrinkage of 38%-43%.
Citation Information
Patent Citations
Hot-rolled wire rod for 1,960MPa-level cable rope galvanized steel wire and production method
CN105671443A
Hot-rolled carbon wire rod for 1770 MPa bridge cable and manufacturing method of hot-rolled carbon wire rod
CN118854173A